Risk Factors for Alzheimer's Disease: Focus on Stress - Alessandra Caruso; Ferdinando Nicoletti; Ferdinando Nicoletti; Alessandra Gaetano; Sergio Scaccianoce (Frontiers Media S.A., 2019)
In vulnerable individuals, chronic and persistent stress is an established risk factor for disorders that are comorbid with Alzheimer's disease (AD), such as hypertension, obesity and metabolic syndrome, and psychiatric disorders. There are no disease-modifying drugs in the treatment of AD, and all phase-3 clinical trials with anti-amyloid drugs (e.g., β- or γ-secretase inhibitors and monoclonal antibodies) did not meet the primary endpoints. There are many reasons for the lack of efficacy of anti-amyloid drugs in AD, the most likely being a late start of treatment, considering that pathophysiological mechanisms underlying synaptic dysfunction and neuronal death begin several decades before the clinical onset of AD. The identification of risk factors is, therefore, an essential step for early treatment of AD with candidate disease-modifying drugs. Preclinical studies suggest that stress, and the resulting activation of the hypothalamic-pituitary-adrenal axis, can induce biochemical abnormalities reminiscent to those found in autoptic brain samples from individuals affected by AD (e.g., increases amyloid precursor protein and tau hyperphosphorylation). In this review, we will critically analyze the current knowledge supporting stress as a potential risk factor for AD.